2015
DOI: 10.3382/ps/peu072
|View full text |Cite
|
Sign up to set email alerts
|

Productive performance of brown-egg laying pullets from hatching to 5 weeks of age as affected by fiber inclusion, feed form, and energy concentration of the diet

Abstract: The effects of fiber inclusion, feed form, and energy concentration of the diet on the growth performance of pullets from hatching to 5 wk age were studied in 2 experiments. In Experiment 1, there was a control diet based on cereals and soybean meal, and 6 extra diets that included 2 or 4% of cereal straw, sugar beet pulp (SBP), or sunflower hulls (SFHs) at the expense (wt/wt) of the whole control diet. From hatching to 5 wk age fiber inclusion increased (P<0.05) ADG and ADFI, and improved (P<0.05) energy effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 44 publications
13
26
0
Order By: Relevance
“…The analytical values of the SFH batch were within the range reported by other authors (Cancalon, 1971;FEDNA, 2010;Guzmán et al, 2015a). The NDF content was 70.0% and the GMD ± GSD was 675 ± 1.68 μm.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The analytical values of the SFH batch were within the range reported by other authors (Cancalon, 1971;FEDNA, 2010;Guzmán et al, 2015a). The NDF content was 70.0% and the GMD ± GSD was 675 ± 1.68 μm.…”
Section: Resultssupporting
confidence: 85%
“…The authors have not found any research comparing the effects of dietary SFH on growth performance of these 2 chicken lines. In pullets, Guzmán et al (2015a) observed a 6.4% increase in ADG from zero to 21 d of age with the inclusion of 2% SFH in the diet. Similar results were reported by González-Alvarado et al (2007) and Jiménez-Moreno et al (2011, 2013a in broilers.…”
Section: Growth Performance and Total Tract Apparent Retention Of Nutmentioning
confidence: 92%
“…The analytical values of the SFH batch were within the range reported by other authors (Cancalon, 1971;FEDNA, 2010;Guzmán et al, 2015a). The NDF content was 70.0% and the GMD ± GSD was 675 ± 1.68 µm.…”
Section: Resultssupporting
confidence: 85%
“…Information available suggests that the beneficial effects of dietary fiber in poultry diet might depend on the birds age with more noticeable effects in young chicks than in pullets and in both type of birds than in laying hens. Research conducted by Guzmán et al (2015a) in which 2% of cereal straw, sugar beet pulp, or SFH were included in pullet diets, showed improved growth performance and energy efficiency with fiber inclusion. However, a further increase to 4% had negative effects on FCR in pullets at 5 wk of age.…”
Section: Growth Performance and Nutrient Digestibilitymentioning
confidence: 99%
“…Two potential nutritional strategies used for increasing the initial body weight (BW) of the hens at the onset of egg production are the feeding of crumbled diets (Frikha et al, 2009a;Gous and Morris, 2001;Saldaña et al, 2015a) and the use of high energy diets (Frikha et al, 2009b;Saldaña et al, 2015b) during the rearing phase. However, Nir et al (1994) and Serrano et al (2013) in broilers and Guzmán et al (2015a) and Saldaña et al (2015a, b) in pullets, have shown that feeding crumbles or pellets reduced the relative weight (g/kg BW) of the gizzard and the development of the gastrointestinal tract (GIT) as compared with feeding mash. Also, when the energy concentration of the diet increases, fiber content decreases, which also reduces GIT development (González-Alvarado et al, 2007;Jiménez-Moreno et al, 2009a;Sacranie et al, 2012).…”
Section: Introductionmentioning
confidence: 99%